Recent advances in mechanochemical production of chemicals and carbon materials from sustainable biomass resources. (September 2020) - Shen, Feng; Xiong, Xinni; Fu, Junyan; Yang, Jirui; Qiu, Mo; Qi, Xinhua; Tsang, Daniel C.W.
Abstract: Biomass resources have been considered as one of the most promising renewable feedstocks to replace fossil resources. However, valorization of biomass is still challenging due to concerns about environmental sustainability and low efficiency of conversion processes. Mechanical ball milling technology, which has emerged as an efficient and environmentally sound alternative to traditional method, can overcome this obstacle to facilitate biomass valorization. Mechanical energy in the ball milling process can induce chemical reactions of biomass in solvent-less/-free conditions. This work reviews the latest advances in the mechanochemical conversion of biomass into chemicals and carbon materials. The initial pretreatment of biomass, catalytic transformation process of biomass, and synthesis of biomass-derived carbon materials (ordered mesoporous carbons, hierarchically porous carbons, carbon/metal composites, etc.) are discussed in detail. Mechanisms, development history, key influencing factors, and technology readiness level of ball milling on biomass valorization are also elucidated. Limitations and opportunities associated with this green technology are highlighted for future research directions. Graphical abstract: Image 1 Highlights: History and mechanism of mechanochemistry are reviewed. The progress of mechanochemistry for lignocellulose pretreatment is analyzed. Mechanochemical-assisted catalytic biomass valorization is reviewed. Functional carbons produced from biomass via mechanical milling is overviewed. Challenge and opportunity for mechanochemistry on biomass utilization are discussed.